Author Correction: Clustering of neuropsychological traits of preschoolers - Treviño, Mario; Beltrán‑Navarro, Beatriz; León, Ricardo Medina‑Coss y; Matute, Esmeralda (Scientific reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.